Die asymptotische Entwicklung für die Verteilungsfunktion der normierten Summen unabhängiger Zufallsgrößen - Survila, P. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:П. Сурвила. Асимптотические разложения для функции распределения нормированной суммы независимых случайных величинP. Survila. Nepriklausomų atsitiktinių dydžių normuotos sumos pasiskirstymo funkcijos asimptotinis išdėstymas